2014
DOI: 10.1186/1756-8722-7-43
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in microRNA target sites modulate risk of lymphoblastic and myeloid leukemias and affect microRNA binding

Abstract: BackgroundMicroRNA dysregulation is a common event in leukemia. Polymorphisms in microRNA-binding sites (miRSNPs) in target genes may alter the strength of microRNA interaction with target transcripts thereby affecting protein levels. In this study we aimed at identifying miRSNPs associated with leukemia risk and assessing impact of these miRSNPs on miRNA binding to target transcripts.MethodsWe analyzed with specialized algorithms the 3′ untranslated regions of 137 leukemia-associated genes and identified 111 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 51 publications
(56 reference statements)
1
15
0
Order By: Relevance
“…As described above, lower levels of p15 INK4b may relieve the inhibition of CDK6, which facilitates pancreatic b-cell proliferation and thus may lower the risk of diabetes. Nevertheless, we observed that the C allele of rs1063192 was associated with increased risk of GDM, consistent with findings of previous studies [30]. We hypothesize that miR-323b-5p may also regulate other genes crucial for b-cell hyperplasia and insulin signaling and that the SNP rs1063192 influences the functions of other underlying regulation factors in the 3 0 UTR of CDKN2B gene.…”
Section: Discussionsupporting
confidence: 91%
“…As described above, lower levels of p15 INK4b may relieve the inhibition of CDK6, which facilitates pancreatic b-cell proliferation and thus may lower the risk of diabetes. Nevertheless, we observed that the C allele of rs1063192 was associated with increased risk of GDM, consistent with findings of previous studies [30]. We hypothesize that miR-323b-5p may also regulate other genes crucial for b-cell hyperplasia and insulin signaling and that the SNP rs1063192 influences the functions of other underlying regulation factors in the 3 0 UTR of CDKN2B gene.…”
Section: Discussionsupporting
confidence: 91%
“…MiR-449 is a member of the miRNA family and has three different isoforms: a, b, and c. These miR-449s shared a cohort of target genes that belong to the E2F transcription factor-retinoblastoma protein pathway [22,23]. Among all miR-449s, miR-449b has been relatively less studied, although its misexpression has been shown in some types of cancer, including bladder cancer [24], colon cancer [25], leukemia [26], endometrial carcinoma [27], and prostate cancer [28].…”
Section: Introductionmentioning
confidence: 99%
“…Although germline polymorphisms are not expected to have a dramatic effect on the cell, as compared to somatic mutations, they may lead to more subtle changes that can gain on significance when several SNPs coexist in a genome. This is illustrated by a trend for a shorter OS in T-cell lymphoma [25] and for a higher risk of ALL and CML [63] with the increasing number of risk genotypes.…”
Section: Discussionmentioning
confidence: 94%
“…The relevance of SNPs in miRNA-binding sites for various types of leukemia was demonstrated recently [63]. In childhood ALL homozygous carriers of variant alleles of ETV6 rs1573613 and TLX1 rs2742038 had an increased ALL risk, while the variant allele of PML rs9479 was associated with reduced risk of ALL.…”
Section: Snps In Mirna-binding Sites In Target Genesmentioning
confidence: 96%